Studi Nalar Hadis Tentang Perceraian (Talak) - Arif Budiman; Fitri Sari (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Marriage is a worship that is very loved by Allah SWT, but in living it, every marriage will experience problems. When the problem cannot be resolved, the last resort each couple will take is divorce (talak). This article aims to explore the traditions of the Prophet SAW. relating to divorce, outlining the law of divorce according to the opinion of scholars and the impact of divorce on child psychology, the theory that will be studied is the theory of developmental psychology by Kayyis Fithri Ajhuri. This research uses descriptive analysis research method by collecting data through library research. The results of this study concluded that in the Hadith of the Prophet SAW. it is said that caution is needed in the pronunciation of the word divorce (talak), because this act is something that the devil likes. Originally, the law of divorce (talak) was khilaful awla, although basically divorce (talak) is permissible in Islam, parents who choose to divorce must pay attention to the impact of the divorce, especially the impact on children. According to Kayyis Fithri Ajhuri, one of the factors that influence the good or bad development of a child is the environment, which in this environment includes family, school, community and the surrounding natural conditions. Divorce is one of the factors that affect the development of a child, because divorce comes from the family itself, namely the parents. One way to reduce the psychological impact of children after a parent's divorce is to love each other and establish good communication between parents and children.